2001
DOI: 10.4049/jimmunol.167.7.3953
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Migration Phenotype of Mitogen-Activated Protein Kinase-Activated Protein Kinase 2−/− Neutrophils in Zigmond Chambers Containing Formyl-Methionyl-Leucyl-Phenylalanine Gradients

Abstract: Time-lapsed video microscopy and confocal imaging were used to study the migration of wild-type (WT) and mitogen-activated protein kinase-activated protein kinase 2 (MK2)−/− mouse neutrophils in Zigmond chambers containing fMLP gradients. Confocal images of polarized WT neutrophils showed an intracellular gradient of phospho-MK2 from the anterior to the posterior region of the neutrophils. Compared with WT neutrophils, MK2−/− neutrophils showed a partial loss of directionality but higher migration speed. Immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 73 publications
4
47
0
Order By: Relevance
“…Remodeling of the actin cytoskeleton is a prerequisite for cell migration, and phosphorylation of Hsp27 by MK2/3 was shown to contribute to cell motility (237). Consistent with this, MK2-deficient neutrophils have defects in chemotaxis and altered chemokinesis (146). The exact contribution of other MK2/3 substrates involved in actin remodeling remains elusive.…”
Section: Mk2/3mentioning
confidence: 73%
“…Remodeling of the actin cytoskeleton is a prerequisite for cell migration, and phosphorylation of Hsp27 by MK2/3 was shown to contribute to cell motility (237). Consistent with this, MK2-deficient neutrophils have defects in chemotaxis and altered chemokinesis (146). The exact contribution of other MK2/3 substrates involved in actin remodeling remains elusive.…”
Section: Mk2/3mentioning
confidence: 73%
“…The targeted deletion of the mk2 gene in mice provided the unexpected result that, although p38 mediates the activation of many similar kinases, MK2 seems to be the key kinase responsible for these p38-dependent biological processes (101,102). Loss of MK2 leads to a defect in lipopolysaccharideinduced synthesis of cytokines such as tumor necrosis factor alpha, interleukin-6, and gamma interferon (101) and also to changes in the migration of mouse embryonic fibroblasts, smooth muscle cells, and neutrophils (75,102,132). Consistent with a role for MK2 in inflammatory responses, MK2-deficient mice show increased susceptibility to Listeria monocytogenes infection (109) and reduced inflammation-mediated neuronal death following focal ischemia (218).…”
Section: Mk2 and -3 Subfamilymentioning
confidence: 99%
“…2/2 mouse embryonic fibroblasts (MEFs) and smooth muscle cells showed reduced migration (Kotlyarov et al, 2002), whereas MK2 2/2 neutrophils showed a partial loss of directionality but higher migration speed (Hannigan et al, 2001).…”
Section: Mk2-dependent Regulation Of Actin Remodeling and Cell Migrationmentioning
confidence: 99%